ANALISIS RESPONSIVITAS BURSA SYARIAH OLEH VARIABEL MAKRO EKONOMI - Pratama, Yoghi Citra (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2012)
The objectives of this study are to analyze the stock responsebecause of M2, exchange rate Rupiah to Dollar and Rate of SBI. The data used in this study is monthly time series data from January 2006-May 2012. Those variabels are JII, M2, exchange rate Rupiah to Dollar and Rate of SBI. Research method used in this study is Vector Error Correction Model (VECM). The cointegration test indicates that among research variabels there is long term equilibrium and simultaneous relationship. The Empirical result of Impulse Response show that the effect of SBI discount rate and M2 is negative and the effect of exchange rate is positive. The result on variance decomposition test, show that the most effect of JII shock is influenced by JII itself.DOI: 10.15408/aiq.v4i2.2548